2018
DOI: 10.1186/s12935-018-0694-9
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-770 affects proliferation and cell cycle transition by directly targeting CDK8 in glioma

Abstract: BackgroundMicroRNAs play crucial roles in tumorigenesis and tumor progression. miR-770 has been reported to be downregulated in several cancers and affects cancer cell proliferation, apoptosis, metastasis and drug resistance. However, the role and underlying molecular mechanism of miR-770 in human glioma remain unknown and need to be further elucidated.MethodsThe expression of miR-770 in glioma tissues and cell lines was measured by quantitative real-time PCR (qRT-PCR) to explore the association of miR-770 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Zhang et al (22) previously demonstrated that miR-770-5p was upregulated in the in vitro model of diabetic nephropathy (DN) and that it may promote the development of DN by regulating podocyte apoptosis through targeting tp53 regulated inhibitor of apoptosis 1. Another previous study revealed that miR-770 inhibits glioma cell proliferation and induces apoptosis through the suppression of the Wnt/β-catenin signaling pathway by targeting cyclin-dependent kinase 8, suggesting that miR-770 may serve a crucial role in glioma progression and may be used as a potential novel target for glioma therapy (23). A recent study demonstrated that when the expression of mir-770-5p is inhibited, cell radiosensitivity is decreased, which suggested that miR-770-5p may be a useful therapeutic target miRNA that sensitizes tumors to radiation through negative regulation of PBK (24).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al (22) previously demonstrated that miR-770-5p was upregulated in the in vitro model of diabetic nephropathy (DN) and that it may promote the development of DN by regulating podocyte apoptosis through targeting tp53 regulated inhibitor of apoptosis 1. Another previous study revealed that miR-770 inhibits glioma cell proliferation and induces apoptosis through the suppression of the Wnt/β-catenin signaling pathway by targeting cyclin-dependent kinase 8, suggesting that miR-770 may serve a crucial role in glioma progression and may be used as a potential novel target for glioma therapy (23). A recent study demonstrated that when the expression of mir-770-5p is inhibited, cell radiosensitivity is decreased, which suggested that miR-770-5p may be a useful therapeutic target miRNA that sensitizes tumors to radiation through negative regulation of PBK (24).…”
Section: Discussionmentioning
confidence: 99%
“…14 Emerging studies indicated that CDK8 was overexpressed and accelerated the progression of tumor cells in multiple cancers, such as colon cancer, 15 pancreatic cancer 16 and glioma. 17 Importantly, Li et al found that CDK8 was associated with sensitivity of PTX in NCI60 cells. 18 But the interaction among circ_0006528, miR-1299 and CDK8 in breast cancer remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This miRNA could also be a useful biomarker for predicting the chemoresistance towards cisplatin in ovarian cancer patients and was found to act as a tumor suppressor by downregulating ERCC2 expression (23). Reduced expression of hsa-miRNA-770-5p was observed in higher stages of glioma (WHO grade III and IV) as compared to lower stages (WHO grade I and II) (19).…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have shown downregulation of miRNA-770-5p in tumors associated with the brain such as gliomas (19) and medulloblastomas (MB) (20). Even amongst different types of brain cancers, the expression levels of hsa-miR-770-5p was significantly lower in MB as compared to astrocytomas (21).…”
Section: Discussionmentioning
confidence: 99%